Bridging the Trust Gap: A Multidimensional Approach to Gen Z’s Literacy in Islamic Finance - Siti Fatmawati; Stella Nathasya Erwianti (Magister Akuntansi Universitas Pancasila, 2026)
Purpose: This study investigates how a multivariable approach, specifically sharia financial literacy education and digital media socialization affects Generation Z's understanding and trust in sharia financial products. Methodology: In this study, a quantitative approach was used along with surveys. Data were collected thru questionnaires distributed to all universities in the City of Bekasi. A total of 203 Generation Z students filled out the questionnaire. The data were analyzed using SEM-PLS to evaluate the relationships between variables and test the proposed hypotheses. Findings: Educational initiatives and digital socialization significantly enhance sharia financial knowledge, which subsequently bolsters consumer trust. Furthermore, sharia financial literacy partially mediates the relationship between education, digital socialization, and trust. Implication: Since digital education and socialization significantly boost Gen Z's understanding and trust, institutions must implement sustainable digital learning programs. Additionally, enhancing transparency, service quality, and accessibility is crucial to advancing sharia financial literacy and inclusion strategies in Indonesia. Originality: This study uniquely applies a multivariable framework combining education and digital socialization to explore Gen Z's trust in sharia finance. It specifically highlights the mediating role of financial literacy among digitally savvy students in Bekasi, a demographic with immense potential for Islamic finance growth.